Viruses of haloarchaea - Luk, AWS; Williams, TJ; Erdmann, S; Thane Papke, R; Cavicchioli, R (Life, 2014)
In hypersaline environments, haloarchaea (halophilic members of the Archaea) are the dominant organisms, and the viruses that infect them, haloarchaeoviruses are at least ten times more abundant. Since their discovery in 1974, described haloarchaeoviruses include head-tailed, pleomorphic, spherical and spindle-shaped morphologies, representing Myoviridae, Siphoviridae, Podoviridae, Pleolipoviridae, Sphaerolipoviridae and Fuselloviridae families. This review overviews current knowledge of haloarchaeoviruses, providing information about classification, morphotypes, macromolecules, life cycles, genetic manipulation and gene regulation, and host-virus responses. In so doing, the review incorporates knowledge from laboratory studies of isolated viruses, field-based studies of environmental samples, and both genomic and metagenomic analyses of haloarchaeoviruses. What emerges is that some haloarchaeoviruses possess unique morphological and life cycle properties, while others share features with other viruses (e.g., bacteriophages). Their interactions with hosts influence community structure and evolution of populations that exist in hypersaline environments as diverse as seawater evaporation ponds, to hot desert or Antarctic lakes. The discoveries of their wide-ranging and important roles in the ecology and evolution of hypersaline communities serves as a strong motivator for future investigations of both laboratory-model and environmental systems.